International Law in the Service of Minority Protection—Hard Law, Soft Law, and a Little Practice - Sándor-Szalay, Elisabeth (International Law From A Central European Perspective, 2022)
With the increase in the number of international organizations directly or indirectly involved in the protection of human rights on the European continent, a kind of competition has developed in recent decades in the field of fundamental rights: By widening the scope of the rights to be protected on the one hand, and by expanding the forms of legal remedies for their protection on the other, the organizations concerned are becoming increasingly integrated into the internal legal systems of the European states. This is why the shortcomings in the effective, systematic protection of minority rights in Europe are quite obvious. It is therefore a contradictory area of law, which must be examined in the light of the potential and the obvious weaknesses of the existing norms and monitoring systems of minority rights. There are tensions and contradictions at many points between the typically individualistic constitutional systems of our time and the concept of minority rights today. It is also clear, however, that it is precisely the highly developed fundamental rights systems that are expected to protect the rights of minorities. The history of the development of minority rights protection, which has its roots in the distant past, provides ample examples of mistakes to be avoided and of the details to which particular attention should be paid in the course of regulation.KEYWORDS: minority rights, international law, European law